Enhancing growth and yield of crops with nutrient‑enriched organic fertilizer at wet and dry seasons in ensuring climate‑smart agriculture - Taiwo B Hammed; Elizabeth O. Oloruntoba; G. R. E. E. Ana (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Rapid nutrient depletion in soils is one of the major problems that affect food production and food security in Sub-Saharan Africa. Studies have linked the growth of food crops with seasonal variation and differences in weather conditions. This study was conducted to assess the effects of various organic fertilizer formulations (OFFs) on the growth and yield of selected crops (Zea mays L.; Glycine max, TX 114 and Dioscorea rotundata Poir) during rainy and dry seasons to ensuring climate-smart agriculture. Method The OFFs used were plant-based (PB), animal-based (AB), rock-based (RB), organic mixture (OM-mixture of PB, AB and RB), synthetic/chemical (SC) while ordinary compost without fortification served as control. Effects of OFFs on growth parameters (number of leaves, plant height, stem girth, leaf area, and crop yield) of maize, yam and soybeans were assessed in plot experiments across the two seasons. Results The RB gave highest growth performances in maize and soybean plots at both seasons when applied at 2.5 t ha−1. It also improved yam growth when applied at 2.5 t ha−1 (rainy season) and 3.0 t ha−1 (dry season) more than any other fertilizer. The largest yield of maize in the dry season was obtained from plots with PB at 2.0 t ha−1. The AB at 2.0 t ha−1 gave the largest soybean yield in the rainy season. Conclusion Organic fertilizers enriched especially with rock-based and plant-based materials have the potential to ameliorate the threat of climate change and seasonal variation to food security.